Fingerprint of dynamical spin-charge correlations in the tunneling spectra of colossal magnetoresistive manganites - Seiro S. S.; Fasano, Yanina; Maggio-Aprile I.; Koller E.; Lortz R.; Fischer Ã˜; Fasano, Yanina (American Physical Society, 2009)
Fil: Fasano, Y. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Université de Genève; Suiza